Attitudes Towards Aloneness During Adolescence: A Person‐Centred Approach. Issue 3 (10th March 2014) - Teppers, Eveline; Luyckx, Koen; Vanhalst, Janne; Klimstra, Theo; Goossens, Luc; Schmidt, Louis A.; Coplan, Robert J.
<x xml:space="preserve">Abstract</x> Benefits and disadvantages of solitude for adolescents are often highlighted. However, research focusing on adolescents' attitudes towards solitude and their associations with such disadvantages or benefits is rather limited. The present study provides a person‐centred perspective on the co‐occurrence of two attitudes towards solitude (i.e., aversion versus affinity) and their associations with coping with loneliness and adjustment. Two independent samples were employed: a sample of 368 freshmen (Mage = 18.22 years, 83.7% female) and another sample of 1, 388 high school students (Mage = 15.72 years, 64.1% female). Cluster analysis uncovered three meaningful clusters in both samples: a true Affinity cluster, a true Aversion cluster, and an Indifferent cluster (having low scores on both attitudes). Whereas the Affinity group more actively confronted their problems when feeling lonely, the Aversion group sought social support more actively. In general, the Indifferent group showed the most optimal profile of psychological adjustment. They used the least passive coping strategies, such as avoidance and depressive reaction patterns. Furthermore, they experienced greater self‐esteem, less depressive symptoms, and lower loneliness as compared to the other two groups. Implications and suggestions for future research are outlined. Copyright © 2014 John Wiley & Sons, Ltd.